Enhanced acidification of global coral reefs driven by regional biogeochemical feedbacks. Issue 15 (5th August 2014) - Cyronak, Tyler; Schulz, Kai G.; Santos, Isaac R.; Eyre, Bradley D.
Abstract Physical uptake of anthropogenic CO2 is the dominant driver of ocean acidification (OA) in the open ocean. Due to expected decreases in calcification and increased dissolution of CaCO3 framework, coral reefs are thought to be highly susceptible to OA. However, biogeochemical processes can influence the pCO2 and pH of coastal ecosystems on diel and seasonal time scales, potentially modifying the long‐term effects of increasing atmospheric CO2. By compiling data from the literature and removing the effects of short‐term variability, we show that the average pCO2 of coral reefs throughout the globe has increased ~3.5‐fold faster than in the open ocean over the past 20 years. This rapid increase in pCO2 has the potential to enhance the acidification and predicted effects of OA on coral reef ecosystems. A simple model demonstrates that potential drivers of elevated pCO2 include additional anthropogenic disturbances beyond increasing global atmospheric CO2 such as enhanced nutrient and organic matter inputs.